Combined performance of hydroxyapatite adsorption and magnetic separation processes for Cd(II) removal from aqueous solution. Issue 5 (25th March 2021) - Shen, Xiaoxiao; Gao, Xuan; Wei, Wei; Zhang, Yong; Zhang, Yong; Ma, Lili; Liu, Huaji; Han, Ruiming; Lin, Jun
Abstract: Cadmium is one of the most toxic cations and harmful to human health and the environment. In this work, a magnetic hydroxyapatite (HAP) modified maghemite (γ-Fe2 O3 ) nanocomposite was successfully prepared as adsorbent for the removal of aqueous Cd(II) with outstanding adsorption performance. The X-ray diffraction analysis (XRD), field emission transmission electron microscope (TEM), vibrating sample magnetometer (VSM) analysis, and Fourier-transform infrared spectroscopy (FTIR) were used for characterization of the adsorbent. The characterization results showed that the obtained nanocomposite was composed of γ-Fe2 O3 and HAP and exhibited a superparamagnetic property. Considering the good separation characteristic after use, the HAP modified γ-Fe2 O3 nanocomposite was used as an adsorbent for the removal of Cd(II) from aqueous solution. The effects of initial pH, adsorbent dosage, contact time, temperature, coexisting ions, and the presence of humic acid on Cd(II) adsorption were investigated. Results showed that the adsorption of Cd(II) was strongly dependent on pH, and the adsorption data could be well fitted by the Langmuir model, and the adsorption kinetics followed the pseudo-second-order model. Compared with pure HAP or γ-Fe2 O3, the prepared nanocomposite had higher adsorption ability toward Cd(II). The maximum adsorbed capacity was found to be 277.78 mg/g, which was much higher than previously reported HAP or γ-Fe2 O3 based adsorbents. Furthermore, the main mechanisms for Cd(II) removal was suggested to be electrostatic interaction, ion-exchange, and surface complexation. Thus, the HAP modified γ-Fe2 O3 nanocomposite showed great potential as a magnetically separable adsorbent for the removal of Cd(II) from polluted water. Graphical Abstract: